Self-Concept and Academic Achievement in Primary School: A Predictive Study - Carrillo-López, Pedro José; Constante Amores, Israel Alexander; Arroyo Resino, Delia; Sánchez-Munilla, María (International Journal of Education in Mathematics, Science and Technology, 2023)
The study of academic achievement continues to be one of the "star" topics in the field of education today because of its great importance as an indicator for assessing educational quality and has therefore been studied from various perspectives. In this regard, the aim of this study was to study which dimensions of self-concept (behavioral, intellectual, physical, lack of anxiety, social or popularity and subjective happiness-life satisfaction) predict performance in each core subjects (Spanish Language and Literature, Mathematics, Natural Sciences, Social Sciences and First Foreign Language (English)). For this purpose, a sample of 116 students from the last cycle of Primary Education (10-12 years) was selected by accessibility and administered a multidimensional Self-Concept Scale. The data were analyzed using the multiple linear regression technique, evaluating the Root Mean Squared Error, statistical power and effect size in all of them. The main results show that intellectual self-concept is the most important predictor of academic achievement. Therefore, schools should be aware of the importance of fostering confidence and expectations of success in students' academic tasks.
Keywords: academic performance; academic self-concept; primary education; multiple linear regression; Scopus; Emerging